Temperature‐Independent Hole Mobility of a Smectic Liquid‐Crystalline Semiconductor based on Band‐Like Conduction. Issue 12 (19th July 2013) - Funahashi, Masahiro; Ishii, Tomohiko; Sonoda, Akinari
Abstract A liquid‐crystalline (LC) phenylterthiophene derivative, which exhibited an ordered smectic phase at room temperature, was purified by vacuum sublimation under a flow of nitrogen. During the sublimation process, thin plates with sizes of 1 mm grew on the surface of the vacuum tube. The crystals exhibited the same X‐ray diffraction patterns as the ordered smectic phase of the LC state that was formed through a conventional recrystallization process by using organic solvents. Because of the removal of chemical impurities, the hole mobility in the ordered smectic phase of the vacuum‐grown thin plates increased to 1.2×10−1 cm2 V−1 s−1 at room temperature, whereas that of the LC precipitates was 7×10−2 cm2 V−1 s−1. The hole mobility in the ordered smectic phase of the vacuum‐sublimated sample was temperature‐independent between 400 and 220 K. The electric‐field dependence of the hole mobility was also very small within this temperature range. The temperature dependence of hole mobility was well‐described by the Hoesterey–Letson model. The hole‐transport characteristics indicate that band‐like conduction affected by the localized states, rather than a charge‐carrier‐hopping mechanism, is a valid mechanism for hole transport in an ordered smectic phase.